A Case of Unresectable Combined Hepatocellular-Cholangiocarcinoma Successfully Treated with Lenvatinib - Takahiro Osuga; Koji Miyanishi; Ryo Ito; Shingo Tanaka; Kota Hamaguchi; Hiroyuki Ohnuma; Kazuyuki Murase; Kohichi Takada; Minoru Nagayama; Yasutoshi Kimura; Taro Sugawara; Shintaro Sugita; et al. (Case Reports in Oncology, 2022)
A 77-year-old man was referred to our hospital because of a hepatic tumor. Blood biochemistry showed elevated serum alfa-fetoprotein, protein induced by vitamin K absence-II, and carbohydrate antigen 19-9 levels. Gd-EOB-DTPA-enhanced magnetic resonance imaging revealed a 95-mm-sized tumor in liver S7. The tumor showed heterogeneous hyperintensity in the arterial phase, slightly washed out from the portal vein phase, and hypointensity in the hepatocellular phase. Post-enlargement segmental resection was performed, and the pathological diagnosis was combined hepatocellular cholangiocarcinoma. Seven months after surgery, multiple liver tumors were found, and biopsy revealed combined hepatocellular-cholangiocarcinoma. Hepatic arterial infusion chemotherapy with cisplatin was initiated. However, the patient developed a pulmonary abscess, which was treated with antibiotics. He then underwent treatment with lenvatinib, 11 months after surgery. At 8 weeks follow-up, a complete response (according to the modified Response Evaluation Criteria in Solid Tumors [RECIST]) and a partial response (RECIST version 1.1) was noted. To the best of our knowledge, thus far, only a single case of lenvatinib treatment of unresectable mixed liver cancer has been reported. In that case, lenvatinib was used as a third-line treatment. The present report is the first to describe lenvatinib as a first-line therapy for unresectable combined hepatocellular-cholangiocarcinoma, which resulted in a meaningful response. This case provides useful insights into the choice of appropriate drug treatment in this disease in the absence of randomized controlled trials of drug treatment.